Riffraff : Poems - Cushman, Stephen, 1956- (Book collections on Project MUSE., 2011)
Stephen CushmanAEs Riffraff embodies the spirit of its title, a Middle English word for ôevery particleö or ôthings of small value.ö In this striking collection, shards and scraps of the impoverished, overlooked, and distastefulùbadgering crows, a prostitute, the speakerAEs own forgotten dreams, toothless dogs rolling in deer offalùbecome occasions to meditate the on rich experiences we too often turn away from. Cushman is the Robert C. Taylor Professor of English at the University of Virginia.